Impact of Social Media Promotion on Customer Purchase Intention of Commercial Banks Services - Shrestha, Sajeeb Kumar (The Batuk, 2020)
Banking sector these days are providing many products/services to the customers in a competitive way. Using social media promotion is a strong tool to reach the prospective and regular customers in the cost effective and time efficient way. So, in this way this research attempts to measure the impact of social media promotion on customer purchase intention of commercial banks services. Descriptive and causal research design was used. Convenience sampling method was used to collect sample. Primary cross- section data were collected. Two hundred samples were approached and data were collected from them. Partial Least Square Structure Equation Modeling (PLS-SEM) was used to measure the research model. The research confirmed customer awareness, customer engagement, product/service perception and trust has significant impact on customer purchase intention of banks services. Banks management should focus on the importance of social media to enhance these factors.